Contribution of Long Non-Coding Rnas (Ccat1, Malat1, and Pandar) in the Pathogenesis of Colorectal Cancer - Ayat B. Al-Ghafari; Halima A. Siddiqui; Hani M. Choudhry; Huda A. Al Doghaither; Huda F. Alshaibi; Alsuﬁani, Hadeil M.; Sawsan A. Rahimulddin (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To assess the relationship between the expression of long non-coding RNAs (lncRNAs), CCAT1, MALAT1, and PANDAR, in CRC patients with varying physical, environmental, and pathophysiological factors. Material and Methods: A case-control study was conducted at King Abdulaziz University (Jeddah, Saudi Arabia). Whole blood was collected from 63 CRC patients and 40 healthy subjects in the period from January to August 2016. Anthropometric measurements were taken and the total RNA was isolated and the expression of lncRNA was determined by real-time polymerase chain reaction. Various software programs, including REST2009 and GraphPad Prism version 7, were used to analyze the different statistical correlations. Results: MALAT1 was significantly highly expressed in CRC female patients, whereas CCAT1 and PANDAR were significantly up-regulated in male CRC patients, as compared with controls. Moreover, in obese CRC patients, CCAT1, MALAT1, and PANDAR expressions were significantly up-regulated, while in overweight CRC patients, only MALAT1 was significantly more highly expressed, compared to controls. There was a slight increase in PANDAR expression in high-grade CRC patients, compared to low-grade patients. Finally, CCAT1 was significantly up-regulated in high fish intake CRC patients and was significantly correlated with smoking status. Conclusion: LncRNAs may contribute to CRC pathogenesis by affecting several physical and environmental factors.